The Populist Radical Right in the US: New Media and the 2018 Arizona Senate Primary - Roberts, Jeremy C. (2020)
This article analyzes the appeal of populist radical right (PRR) politics in the US after the election of Donald Trump. Specifically, I seek to explain how new media helps politicians representing the PRR secure support in Republican primaries. Using an online survey of 1052 Arizona Republicans in the lead-up to the August 2018 Senate primary, I evaluate support for three candidates: Rep. Martha McSally, former Maricopa County Sheriff Joe Arpaio, and Kelli Ward, a physician. The findings highlight a bifurcation in the drivers for support of PRR candidacies: Skepticism of immigration drives the Arpaio vote, while use of social media news and belief in party convergence mobilize Ward’s support. The results demonstrate that support for PRR politicians in the Arizona primary is concentrated in two groups, anti-immigrant and anti-establishment, and that the anti-establishment voters are more likely to access news on social media. These findings indicate that social media news consumption does shape voter perceptions about mainstream parties favorably for the PRR.